Comparison of the effectiveness between kataria and paedfusor models of target controlled infusion (TCI) during anaesthesia in elective paediatric surgery - Mansor, Azelia (2017)
Background: Kataria and Paedfusor are two validated target controlled infusion (TCI) models for propofol in paediatric population. The aim of this study was to compare the effectiveness of these two different TCI models for propofol in paediatric age group during elective surgery. Methods: 38 patients, aged 3-12 year-old, classified under ASA I and II, who underwent elective surgery under general anaesthesia, were randomised into two groups; Group Kataria (n=19) and Group Paedfusor (n=19). All patients received 1 mcg/kg loading dose of intravenous (IV) remifentanil over 1 minute 15 seconds and followed with infusion at 0.1 to 1 mcg/kg/min. Then, both groups were induced at plasma concentration (Cpt) propofol of 6 mcg/ml using respective model and maintained with Cpt between 3 to 6 mcg/ml guided by bispectral index (BIS) between 40-60. Remifentanil was maintained between 0.1 to 1 mcg/kg/min. Success rate of induction, induction time, recovery time and plasma concentration (Cp) at recovery were recorded for statistical analysis.Results: Both groups were successfully induced with propofol Cpt of 6mcg/ml. There were no significant difference in induction and recovery time between these two groups. The plasma concentration at recovery in Kataria group was significantly lower than Paedfusor group [1.48 (0.11) mcg/ml vs 1.59 (0.14) mcg/ml, p=0.01]. Conclusion: TCI propofol for paediatric patients using Kataria and Paedfusor models were equally effective in success rate of induction, induction time and recovery time. Only plasma concentration at recovery was lower in Kataria group.